Estudio de viabilidad de alternativas para el aprovechamiento del mango tommy y de azúcar rechazado para la comercialización en la empresa frutarona s.a.s. (2023)
The purpose of this monograph as a degree project was to study the feasibility of new product alternatives such as business models, based on mango pulp, seed and peel, especially identifying the coefficient of loss of rejected mango crops for commercialization either national or international. The main objective of this research is to seek the creation of new products derived from the sub-properties of mango, giving it the appropriate use that corresponds to this fruit, that is, (mango), seeking satisfactory results in terms of the viability that exists in the creation. Of new products made by the company Frutayrona SAS, using the rejected mango for its commercialization; within the development of the investigation, internal questions were asked to the administrative staff of the company and the export coordinator, giving them percentages and exact figures of what the crop production has been in the year. Mango is one of the fruits that is widely accepted in the national and international market, but it presents numerous problems to be marketed as fresh fruit, for reasons of care at harvest, packaging and shipping, this reason leaves producers as an alternative commercialization of products derived from mango, that is, the commercialization of the pulp, peel and seeds. From this, it seeks to innovate with the company frutayrona s.a.s in products giving utility to each fruit lost in the export and commercialization batches, that is to say, the mangoes that at the time are innocuous, but present limitations in size or mechanical damage that make difficult to sell and in turn in cases in which maturity is advanced and would not support the entire period of distribution and sale. The proposal raised for this work is to find a method of 100% use of the mangoes that cannot go on the market, but can be put to good use by creating innovative products such as: compotes, juices, nectars, jams, wines, sweets; among others.